Can professional football players adapt to air pollution? Evidence from China - Qin, Y.; Wu, J.; Zhang, R. (Journal of Sports Economics, 2022)
In this paper, we study the impact of air pollution on Chinese professional football players` performance. Our primary research question is whether the negative effects of air pollution can be mitigated by adaptation, and which cohort of players can have higher adaptability. We find that a higher pollution level during the game, relative to the adapted pollution level in players` home cities, has a negative and significant impact on the players` efforts and accuracy. The impact of non-adapted air pollution can be greatly offset by the home advantage, but not by personal attributes such as the higher ability.